The effects of calcium-to-phosphorus ratio on the densification and mechanical properties of hydroxyapatite ceramic - Tan C.Y.; Singh R.; Teh Y.C.; Tan Y.M.; Yap B.K. (Blackwell Publishing Ltd, 2023)
Density (specific gravity); Elastic moduli; Fracture; Fracture toughness; Hydroxyapatite; Mechanical properties; Orthophosphoric acid; Particle size; Phosphorus; Powders; Precipitation (chemical); Sintering; Toughness; Vickers hardness; Calcium deficients; High temperature; Hydroxyapatite ceramics; Microstructural examination; NO decomposition; Relative density; Wet-chemical precipitation; Young's Modulus; Calcium